THE ROLE AND SOCIO-ECOLOGICAL FUNCTIONALITY OF TAX TOOLS IN THE CONTEXT OF THE INDUSTRY 4.0 PARADIGM - M. V. Karp; A. V. Zakharova; L. S. Samodelko (Вестник университета)
The tax system of any state is designed to ensure and regulate economic processes in order to support development and solve socio-ecological and economic problems. The tools of the tax legislation of the Russian Federation, being primarily a mechanism for generating state revenues, have an impact on the development of organizations, industries, industries by creating demand for goods, works, and services, regulating prices and inflationary processes, as well as maintaining social justice in society. However, the revision of the current tax tools with the analysis of current trends is quite rare, while the change of economic development paradigms requires constant attention and timely adjustment. The article considers the specified problems and selects ways to express the socio-ecological functional of taxes in the context of industrial transformation. Based on the analysis of the current legislation, the authors highlight tax instruments that have an impact on economic entities in the context of the development of automation and data exchange, evaluate their effectiveness. The results of the study can be used to adapt the tax policy of the state in the context of the “Industry 4.0” paradigm.